The renal function in men with hypertension in conditions of purine and carbohydrate metabolism disorders - O. V. Dudko; M. Yu. Kolesnyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. To assess the condition of renal function in hypertensive men in conditions of disorders of purine and carbohydrate metabolism